Bilateral tension pneumothorax after acupuncture. (19th April 2018) - Mohammad, Nurashikin
Abstract : Acupuncture is an ancient complementary medicine which is currently used worldwide. Many serious adverse events have been reported which include a spectrum of mild-to-fatal complications. However, the level of awareness with regard to complications is still low both to physicians and patients. We report a 63-year-old who presented with acute shortness of breath 2 hours after having had acupuncture. On examination, there was absent breath sound heard on the left lung and slightly reduced breath sound on the right lung. She had type 1 respiratory failure. Urgent chest radiograph confirmed bilateral pneumothorax which was more severe on the left with tension pneumothorax and mediastinal shift. Chest tubes were inserted bilaterally after failed needle aspiration attempts. Subsequently, the pneumothoraces resolved, and she was discharged well. The bilateral pneumothoraces caused by acupuncture were curable but could have been potentially fatal if diagnosis was delayed. This case report adds to the limited current literature on the complications of acupuncture leading to bilateral pneumothoraces.